PEMBELAJARAN SNOWBALL THROWING DITINJAU DARI GAYA BELAJAR EKSTROVERT-INTROVERT - Sulaiman, Sulaiman (JURNAL e-DuMath, 2018)
The low yield of mathematics learning in SMP Negeri 1 Adiluwih due to the liveliness and motivation of students in participating in learning is still not visible .. Low and high mathematics learning outcomes are also influenced by several factors, including the students learning style. One effort that can be done to overcome these problems is to use cooperative learning model snowball throwing.The purpose of this study was to determine the results of students mathematics learning through cooperative learning model snowball throwing in terms of students learning styles.The population of this research is all class VIII SMP Negeri 1 Adiluwih totaling 285 students, divided into 9 classes. The sample was 70 students consisting of 35 students to a class of 35 students for the experimental and control classes were obtained bytechnique. cluster random samplingThe instrument used was a questionnaire and student mathematics achievement test. Data analysis techniques used in this study is a party t-test and t-test two parties.Based on t-test calculation of the two parties to the students learning style extrovert, shows thitung = 3.07 and ttable = 2.021 at significance level of 5% that  thitung > ttable (3.07> 2,021), then H0 is rejected and H1 received. For the t-test of the parties to the students learning style extrovert show thitung = 3.07 and ttable = 1.684 at significance level of 5% that  thitung > ttable (3.07> 1.684), then H0 is rejected and H1 accepted. T-test calculation of the two parties to the students learning style introvert show thitung = -0.87 and ttable = -2.069 at a significance level of 5% that  thitung > ttable (-0.87> -2.069), then H0 is  rejected and H1  accepted. For the t-test for students learning styles  introvert  show thitung = -0.87 and ttable = 1.714 at significance level of 5% that  thitung <ttable   (-0.87 <1.714), then H0 is   rejected and H1 accepted. Key words: snowball throwing,learning style, ekstrovert, extrovert